The Vascular Convolutions-Papillary Endothelial Hyperplasia - Anubha Bajaj (Journal of Dermatologic Research And Therapy, 2020)
Intravascular papillary endothelial hyperplasia is an exceptional, benign, inflammatory, vascular neoplasm delineating papillary configuration engendered from reactive proliferation of damaged endothelial cells, while being confined to a thrombus. Initially scripted by Pierre Mason in 1923, the tumefaction was denominated as an intra-luminal lesion within an ulcerated, haemorrhoidal vein and designated as “hemangio-endotheliome’ vegetant’ intravasculaire”(1). The neoplasm is additionally nomenclated as Masson’s tumour, Masson’s pseudo-angiosarcoma, endovascularite proliferante thrombopoietique, intravenous atypical vascular proliferation, intravascular angiomatosis, vascular angiomatosis, intravascular endothelial proliferation, reactive papillary endothelial hyperplasia or intravascular papillary endothelial hyperplasia. The papillary neoplasm is associated with deposition of fibrin and thrombotic substances within a painful, ulcerated.
Keywords: Papillary Endothelial Hyperplasia